Hijab and Burqa in Islamic Fashion System: فرات جمال حسن العتابي (Al-Academy, 2020)
Most of the propositions and researches that dealt with fashions in the Middle East, specifically this region from the world, from a historical perspective have not been sufficient, and were characterized by many aspects of immature thinking, in addition, they have been varied in quality. This can be attributed to many factors including: the focus in the field of researches and Middle East studies is on languages, arts, history, and political thinking of the region. Other factors are the information asymmetry, the differences in sources and references, in addition to differences in the scientific value of these sources added to the difficulty of gathering them at the same time especially that these sources are scattered in many places whether in the literary and non-literary texts written with many Middle Eastern languages. Starting from this standpoint, this study seeks to address the topic of hijab and burqa from the Islamic perspective from a historical analytical viewpoint and their influence in the Islamic fashion system and their development over successive historical periods within certain geographical frameworks, as they are part of the Islamic dress code, let alone being influenced by social, religious, aesthetic, economic and political levels according to the reflection standards on the spirit of the society over the years, based on a group of Islamic documents, manuscripts drawings and paintings, in addition to some important documents about Arab clothes and fashions in the manuscripts, paintings and ornamental pictures, as well as the illustrations in the Arab books that date back to the period between 5thc. and 20th c.From this standpoint, this study seeks to address the topic of the “AL- Burqaa” and the veil in the Islamic perspective, from a historical and analytical point of view, and its impact on the Islamic system and its development through successive historical periods in certain geographical frameworks, as part of the Islamic clothing system, as well as its influence on social, or religious levels , Or aesthetic, economic and political, according to the criteria of reflection on the spirit of society over the years. Depending on a set of documents, manuscripts, drawings, and Islamic paintings, as well as some important data on Arab clothing and fashion in manuscripts, paintings, and decorative pictures, and illustrations found in Arabic books dating back to the period between the fifth century and the twentieth century AD. Among urban and rural residents, or in different societies and social groups, whether Arabs or Muslims.